Invisible helix - Higashino, Keigo, 1958- (Higashino, Keigo, 1958- Detective Galileo novels., 2024)
Detective Galileo, Keigo Higashino's best loved character from The Devotion of Suspect X, returns in a case where hidden history, an impossible crime, are linked by nearly invisible threads in surprising ways. The body of a young man is found floating in Tokyo Bay. But his death was no accident -- Ryota Uetsuji was shot. He'd been reported missing the week before by his live-in girlfriend Sonoka Shimauchi, but when detectives from the Homicide Squad go to interview her, she is nowhere to be found. She's taken time off from work, clothes and effects are missing from the apartment she shared. And when the detectives learn that she was the victim of domestic abuse, they presume that she was the killer. But her alibi is airtight -- she was hours away in Kyoto when Ryota disappeared, forcing Detectives Kusanagi and Utsumi to restart their investigation. But if Sonoko didn't kill her abusive lover, then who did? A thin thread of association leads them to their old consultant, brilliant physicist Manabu Yukawa, known in the department as "Detective Galileo." With Sonoko still missing, the detectives investigate other threads of association -- an eccentric artist, who was Sonoko's mother figure after her own single mother passed; and an older woman who is the owner of a hostess club. And how is Sonoko continuing to stay one step ahead of the police searching for her? It's up to Galileo to find the nearly hidden threads of history and coincidence that connect the people around the bloody murder-- which, surprisingly, connect to his own traumatic past -- to unravel not merely the facts of the crime but the helix that ties them all together.